The Influence of Digital Literacy, Peer Influence, and Security Training Effectiveness on Cybersecurity Behavior in the Banking and Finance Industry - Ibrahim, Mozart Malik; Shabrina, Fildzah; Marnilin, Feni; Hendratni, Tyahya Whisnu; Apramilda, Riesna; Nugroho, Judianto Tjahjo (Yayasan Gema Bina Nusantara, 2025)
The study's main goal is to investigate how the three factors, digital literacy, peer influence, and security training, affect the cybersecurity behavior of the bank and finance industry's personnel. The research applied a quantitative explanatory method with a sample of 150 employees from banks, financial institutions, and fintech companies. The sample was drawn purposefully from the population. The multiple linear regression analysis results show that the independent variables digital literacy, peer influence, and security training all have a positive and significant impact on the dependent variable, which is cybersecurity behavior. The research not only makes a theoretical contribution to the discussion about human motivations in cybersecurity but also provides recommendations for the banking and finance industry that include increasing the level of digital literacy activities, encouraging positive social influences at workplaces, and maximizing the effectiveness of security training as a risk management strategy.